Government Legal Policy to Deal with Cases of Human Rights Violations in Indonesia - Nuril Ika Fajriyah; Suwandi Suwandi; Aunur Rofiq (Legitimasi: Jurnal Hukum Pidana dan Politik Hukum, 2024)
Cases of gross human rights violations are complex and sensitive issues in Indonesian legal politics. With a historical backdrop that includes authoritarian times and armed conflict, governments are faced with serious challenges. Transitional Theory of Justice offers a framework for addressing these issues through courts, reparations, truth and reconciliation, and institutional reform. However, policy implementation requires consideration of international pressure, victim protection, civil society participation, and human rights education. Governments are faced with a dilemma between accountability and reconciliation, with the need to maintain a balance between justice and peace. In addition, it is necessary to consider the political implications of government actions, while institutional reform and sustainable approaches are key in addressing gross human rights violations.